Astroglial Plasticity in the Hippocampus is Affected by Chronic Psychosocial Stress and Concomitant Fluoxetine Treatment - Czéh, Boldizsár; Simon, Mária; Schmelting, Barthel; Hiemke, Christoph; Fuchs, Eberhard (Neuropsychopharmacology (New York, N.Y.), 2006)
Analysis of post-mortem tissue from patients with affective disorders has revealed a decreased number of glial cells in several brain areas. Here, we examined whether long-term psychosocial stress influences the number and morphology of hippocampal astrocytes in an animal model with high validity for research on the pathophysiology of major depression. Adult male tree shrews were submitted to 5 weeks of psychosocial stress, after which immunocytochemical and quantitative stereological techniques were used to estimate the total number and somal volume of glial fibrillary acidic protein-positive astrocytes in the hippocampal formation. Stress significantly decreased both the number (-25%) and somal volume (-25%) of astroglia, effects that correlated notably with the stress-induced hippocampal volume reduction. Additionally, we examined whether antidepressant treatment with fluoxetine, a selective serotonin reuptake inhibitor, offered protection from these stress-induced effects. Animals were subjected to 7 days of psychosocial stress before the onset of daily oral administration of fluoxetine (15 mg/kg per day), with stress continued throughout the 28-day treatment period. Fluoxetine treatment prevented the stress-induced numerical decrease of astrocytes, but had no counteracting effect on somal volume shrinkage. In nonstressed animals, fluoxetine treatment had no effect on the number of astrocytes, but stress exposure significantly reduced their somal volumes (-20%). These notable changes of astroglial structural plasticity in response to stress and antidepressant treatment support the notion that glial changes may contribute to the pathophysiology of affective disorders as well as to the cellular actions of antidepressants.